Long-Term Survival Rate in Patients With Acute Respiratory Failure Treated With Noninvasive Ventilation in Ordinary Wards. Issue 12 (December 2016) - Cabrini, Luca; Landoni, Giovanni; Bocchino, Speranza; Lembo, Rosalba; Monti, Giacomo; Greco, Massimiliano; Zambon, Massimo; Colombo, Sergio; Pasin, Laura; Beretta, Luigi; Zangrillo, Alberto
Abstract : Objective: Noninvasive ventilation is a life-saving technique increasingly used to treat acute respiratory failure. Noninvasive ventilation has been applied mostly in ICUs, but several reasons brought to an increasing application of noninvasive ventilation in ordinary wards. Few articles evaluated the outcomes of patients receiving noninvasive ventilation including long-term follow-up. The aim of the present study was to assess 1-year survival rate of patients treated with noninvasive ventilation outside the ICU for acute respiratory failure of heterogeneous causes and to identify the predictors of long-term mortality. Design: Prospective, observational, pragmatic study. Setting: Ordinary wards of a teaching hospital. Patients: Consecutive patients treated with noninvasive ventilation for acute respiratory failure. Interventions: None. Measurements and Main Results: Two-hundred and twenty-patients were enrolled. Mortality rates at 30-day, 90-days, and 1-year follow-up were 20%, 26%, and 34%. When excluding patients with "do-not-resuscitate" status, mortality rates were 13%, 19%, and 28%. The multivariate analyses identified solid cancer, pneumonia in hematologic patients, and do-not-resuscitate status as independent predictors of mortality with postoperative acute respiratory failure associated with improved survival. The same predictors were confirmed when excluding do-not-resuscitate patients from the analyses. Conclusions: Noninvasive ventilation applied in ordinary wards was effective, with long-term outcomes not different from those reported for ICU settings. Solid cancer, pneumonia in hematologic malignancies, and do-not-resuscitate status predicted mortality, whereas patients with postoperative acute respiratory failure had the best survival rate. Additional studies are required to evaluate noninvasive ventilation efficacy in the wards compared with ICU. Abstract : Supplemental Digital Content is available in the text.